(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Tolerance of Trichoderma species collected from tea plantation to fungicides was evaluated in vitro using poisoned food method. Fungicides like Carbendazim 50 WP, Copperoxychloride 50 WP, Hexaconazole 5 EC, and Propiconazole 25 EC were used at two lower and two upper of recommended doses. The growth of T. harzianum was mostly inhibited by the Carbendazim 50 WP and Propiconazole 25 EC with the recommended doses; while T. viride could grow easily with the said doses. Both species of Trichoderma grew easily in medium containing Copperoxychloride even at highest doses. Hexaconazole 5 EC proved to be highly toxic with no growth of Trichoderma harzianum in treatments containing 40.0 and 42.05 ppm. At highest concentration (42.5 ppm) of Hexaconazole 5 EC, T. viride grew after 72 hours of incubation. It was 14.44% over the control on 4th day of plating. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11758 Bangladesh J. Agril. Res. 36(4): 677-683, December 2011